UPAYA PENGENDALIAN GAS HIDROGEN SULFIDA (H2S) DI INSTALASI BIOGAS PABRIK KELAPA SAWIT PT. RAMA JAYA PRAMUKTI KECAMATAN TAPUNG - Jhon Prengky; Yusni Ikhwan Siregar; Bayhakki Bayhakki (JURNAL SENPLING MULTIDISIPLIN INDONESIA, 2024)
Hydrogen Sulfide or H2S is a gas that is toxic and dangerous, especially for human health. The biogas processing process produces several gases, namely CH4,CO2, NH3 and H2S gas which are not utilized, so that H2S gas will be disposed of together with the waste.. This study aims to determine the concentration of H2S in the ambient air around the work biogas area, to describe the level of knowledge and compliance of workers in the use of personal protective equipment (PPE), and to determine the H2S gas control efforts carried out in biogas installations. This research was conducted by taking ambient air samples to determine the concentration of H2S in the air. Descriptive analysis is used to describe the level of knowledge and compliance of workers in the use of PPE and to determine the H2S control efforts carried out. The results showed that the concentration of H2S in the air was 0.032 ppm at the biogas erea and lesser 0.003 ppm at the waste poll area. The air quality around the biogas area still exceeds the standard limit so it is not safe for the environment but according to OSHA regulations the H2S concentration of 0.01 ppm to 1 ppm still has no health impact so that the air quality around the biogas is safe for workers. The level of knowledge in use obtained a good knowledge value of 60% and a bad knowledge value of 40%. The level of compliance in the use of PPE obtained compliance results of 67.3% while the non-compliance value was 33.3%. Efforts to control H2S gas are carried out based on the implementation of Government Regulation Number 50 of 2012 concerning the OHS Management system which includes technical control, administrative control in the form of periodic monitoring and socialization to workers.